Remedies for specific performance for land contract: legal development - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah (2015)
The paper discusses the relief of specific performance (SP) and deals with types and nature of contract that may be ordered by the court to be specifically performed and those that cannot be specifically performed. Specifically, the paper analyses the circumstances in which the courts decide to grant SP and not to grant SP for land contract. Under the law, the remedy of SP is discretionary and scuh discretion to be exercised according to well established principles. It is found out that the right to sue for SP in equity is quite distict from the cause of action at common law. SP is granted when there are circumstances justifying it. The grant of SP is always subject to conditions.SP is said to be the best remedy for breach of immovable contract.